The Conceptual Framework of Digital Supply Chain for Research Management in Higher Education Institutions - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aimed is to find and to evaluate the conceptual framework of supply chain in digital for research management in higher education institute. The research sample totaling ten experts consisted of ten experts consisted of five experts on supply chain , two experts on information technology and three experts on eeducational research and evaluation. The employed research instrument is a questionnaire. Statistics employed for data analysis are mean and standard deviation. The research found that the conceptual framework of supply chain in digital for research management in higher education institute comprising of seven principal components, namely ,main element,suppliers , university ,customers ,consumers ,satisfaction and feedback. The results from experts agreement the conceptual framework of supply chain in digital for research management in higher education institute. was a high level. (=3.65,S.D.= 0.82), that mean the conceptual framework to may be applies in support the tasks.